2019
DOI: 10.3897/alpento.3.28366
|View full text |Cite
|
Sign up to set email alerts
|

Temporal niche partitioning of Swiss black scavenger flies in relation to season and substrate age (Diptera, Sepsidae)

Abstract: Understanding why and how multiple species manage to coexist represents a primary goal of ecological and evolutionary research. This is of particular relevance for communities that depend on resource rich ephemeral habitats that are prone to high intra- and interspecific competition. Black scavenger flies (Diptera: Sepsidae) are common and abundant acalyptrate flies associated with livestock dung decomposition in human-influenced agricultural grasslands worldwide. Several widespread sepsid species with apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Although all species investigated here (except T. minor) commonly co-occur on livestock excrements (at least in Central Europe), the mechanisms that allow more than 10 closely related species of the genus Sepsis to co-exist in the same habitat remain contentious even after this study. Previous studies suggested little larval substrate specialization (Laux et al 2019) and only minor geographic, altitudinal or seasonal (including diurnal) variation in occurrence (Rohner et al 2014(Rohner et al , 2015(Rohner et al , 2019. Therefore these species have largely overlapping ecological niches.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although all species investigated here (except T. minor) commonly co-occur on livestock excrements (at least in Central Europe), the mechanisms that allow more than 10 closely related species of the genus Sepsis to co-exist in the same habitat remain contentious even after this study. Previous studies suggested little larval substrate specialization (Laux et al 2019) and only minor geographic, altitudinal or seasonal (including diurnal) variation in occurrence (Rohner et al 2014(Rohner et al , 2015(Rohner et al , 2019. Therefore these species have largely overlapping ecological niches.…”
Section: Discussionmentioning
confidence: 97%
“…Traits characterizing male and female mating behavior furthermore align well along the slow-fast reproductive continuum (Table 2). The most abundant and relatively large species S. cynipsea, S. punctum and S. thoracica (Rohner et al 2015(Rohner et al , 2019Busso and Blanckenhorn 2018a; Fig. 1) feature clutch sizes of around 45 -60 large eggs (ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, we found little variation in the preferences for different types of dung and performance of 7 (9) closely related and common dung fl ies. Preferences for different types of dung thus cannot account for, or defi ne, the niche differentiation of these species that regularly co-exist in the same pastures or other sites in Switzerland and elsewhere (Rohner et al, 2014(Rohner et al, , 2015(Rohner et al, , 2019. We further found that oviposition preference of adults correlated with larval performance, indicating the oviposition behaviour of gravid fl y females is adaptive.…”
Section: Discussionmentioning
confidence: 71%